2019
DOI: 10.1111/joor.12755
|View full text |Cite
|
Sign up to set email alerts
|

A survey on the prevalence and risk indicators of erosive tooth wear among adolescents in Guangzhou, South China

Abstract: The term "tooth wear" (TW) is used to describe the loss of dental hard tissues (Viz. enamel and dentine) caused by friction between occlusal surfaces and food during masticatory or non-masticatory processes; between the occlusal surfaces of opposing teeth, with no involvement of dental caries or trauma; or by demineralisation through the action of nonbacterial extrinsic or intrinsic acids. 1 TW can be divided into the subtypes mechanical wear(attrition and abrasion) and chemical wear(erosion, erosive tooth wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Either self‐administered questionnaires (n = 46) or structured interviews (n = 5) were used to analyse dietary patterns and habits, with one study utilising a single application 24‐hour food recall 33 . Of these, questionnaires were validated for adolescents in only 11 studies, 28,34‐43 whereas the types of food/beverages evaluated were validated in five studies 44‐48 . Ten studies validated for both 49‐58 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Either self‐administered questionnaires (n = 46) or structured interviews (n = 5) were used to analyse dietary patterns and habits, with one study utilising a single application 24‐hour food recall 33 . Of these, questionnaires were validated for adolescents in only 11 studies, 28,34‐43 whereas the types of food/beverages evaluated were validated in five studies 44‐48 . Ten studies validated for both 49‐58 .…”
Section: Resultsmentioning
confidence: 99%
“…No significant associations were identified between DE incidence and timing of dietary acid intake at bedtime, before or after brushing 78 . Five cross‐sectional studies found a directly proportional relationship between the consumption of acidic drinks or foods at bedtime and DE 45,52,53,59,62 . One of these identified lemon juice, carbonated drinks, lemon, and sour candy to be the most harmful 53 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a recent meta-analysis, the current world-wide prevalence of ETW among children and adolescents is 30% and it has been suggested to be increasing [3,4]. Research on the topic in Asian countries is inconclusive [2], and the prevalence figures vary between low and moderate [5][6][7]. Even though ETW has also gained interest recently in Asian countries, to our knowledge, no studies concerning ETW among Nepalese children and adolescents has been done.…”
Section: Introductionmentioning
confidence: 99%